The Analysis of Incentive Effect on Motivation and Employee Performance at PT Jamsostek (Persero) Medan Branch - Rosita Rosita; Hengky Kosasih; Erina Erina (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
The purpose of this study is to determine and explain the significance of the effect of Material Incentives and Non-Material Incentives on Work Motivation, the effect of Material Incentives and Non-Material Incentives on Employee Performance, and the effect of Work Motivation on Employee Performance. The type of research used in this research is explanatory research, and the research method used is quantitative. The population in this study amounted to 36 employees of PT Jamsostek (Persero) Medan Branch. The number of samples was 36 employees using the Population sampling technique. The data was processed using a computer program SPSS 20 for windows. Based on the results of inferential analysis using path analysis which shows the significant value of F, namely 0.000 <0.05 (alpha). The path coefficient values are 0.345 and 0.479 for Material Incentives (X1) and Non-Material Incentives (X2) on Work Motivation ( Y1), the path coefficient value is 0.322 and 0.316 for Material Incentives (X1) and Non-Material Incentives (X2) on Employee Performance (Y2). The path coefficient value is 0.346 for Work Motivation (Y1) on Employee Performance (Y2). Likewise, the value of Adjusted R Square is 0.497 for Work Motivation (Y1) and 0.686 for Employee Performance (Y2). It shows that the Material Incentive and Non-Material Incentive variables significantly affect Work Motivation and Employee Performance, either directly or indirectly.